Characterisation and cryopreservation of Bapedi ram semen in tris egg yolk extender supplemented with phosphatidylcholine - Mafolo, Kgaogelo Stimela (My University, 2018)
The study was conducted to determine the macroscopic and microscopic raw semen characteristics of Bapedi rams, to evaluate the effect of different egg yolk (EY) concentrations in Tris-based extenders on cryopreservation of Bapedi ram semen and to determine the effect of supplementing different phosphatidylcholine (PC) concentrations in Tris-based extenders with or without egg yolk on cryopreservation of Bapedi ram semen. Semen ejaculates were collected from four matured Bapedi rams aged 2-4 years using artificial vagina (AV) and pooled to eliminate individual differences. The first experiment was performed to characterise Bapedi ram semen parameters immediately after semen collection. The macroscopic semen parameters such as volume, pH and concentration and microscopic semen parameters such as motility, viability and morphology, membrane integrity and acrosome integrity were evaluated. The experiment was replicated 8 times and the data was subjected to descriptive statistics. The second experiment evaluated the effect of Tris-based extenders with five different EY concentrations (0, 5, 10, 15 and 20 %) on the microscopic quality of cryopreserved Bapedi ram semen. The treatments were subjected to a Completely Randomized Design (CRD) and replicated 4 times. The third experiment evaluated the effects of different PC concentrations supplemented to Tris-based extenders with or without 10% EY and the PC was added as liposomes. The experiment was a 2 x 4 factorial design in a CRD with two concentrations of EY: 0 and 10 %, and four concentrations of PC: 0, 0.25, 0.50, 0.75 mg/ml in Tris-based extenders. Pooled semen samples were divided into 5 and 8 aliquots to comply with objective 2 and objective 3, respectively. The semen aliquots were diluted with Tris-based extenders and equilibrated in a refrigerator at 5°C for another 4 hours. The semen was frozen using a programmable freezer and plunged into liquid nitrogen tank (-196°C).The volume, sperm concentration and pH of Bapedi ram semen ranged between 0.4-1.5 ml, 0.52-8.84 × 109 sperm/ml, and 5-7, respectively. The average total motility (TM), progressive motility (PM) and rapid motility (RM) characteristics were 85.95±2.58 %, 29.33±2.11 % and 39.47±4.99 %, respectively. The results for the mean percentage live spermatozoa, abnormalities, intact membrane and intact acrosome were 70.19±2.29 %, 2.50±1.34 %, 72.39±1.71 % and 75.37±5.39 %, respectively. There was a general decrease trends in frozen-thawed motility characteristics such as TM, PM and RM as compared to raw semen (p<0.05). The frozen-thawed semen in Tris-based extenders with 10, 15 and 20% EY concentrations resulted in significantly (p<0.05) higher TM, PM and RM motility characteristics compared to 0 and 5%. The percentage of live spermatozoa, membrane and acrosome integrities were found higher in raw semen than in frozen–thawed semen of respective extenders (p<0.05). The supplementation of PC in extenders either with or without EY did not improve the TM, PM and RM parameters (p>0.05). The membrane integrity in extenders either with or without EY were not influenced by the supplementation PC after freezing and thawing (p>0.05). The supplementation of PC in treatments with EY did not improve the acrosome integrity (p>0.05). Interestingly, the supplementation 0.75 mg/ml PC resulted in acrosome integrity that was not significantly different (P>0.05) to treatments with EY. In conclusion, the macroscopic and microscopic semen parameters of raw Bapedi ram semen were characterized. The use of 10% EY concentration resulted in higher motility parameters and membrane integrity of frozen-thawed Bapedi ram semen. However, 20% EY resulted in higher acrosome integrity of frozen-thawed Bapedi ram semen. The supplementation of PC in extenders in extenders with or without EY did not improve the motility parameters, percentage live spermatozoa and membrane integrity. However, the acrosome integrity was improved in extenders without EY supplemented with 0.75 mg/ml PC
Thesis (M.Sc. (Animal Production)) -- University of Limpopo, 2018
Keywords: Egg yolk; Eggs